Characterization of adult stem/progenitor cell populations from bone marrow in a three-dimensional collagen gel culture system. - Claros-Gil, Silvia; Rodríguez-Losada, Noela; Cruz, Encarnación; Guerado-Parra, Enrique; Becerra-Ratia, José; Andrades-Gómez, José Antonio (Sage Publications, 2012)
Stem cell transplantation therapy using mesenchymal stem cells (MSCs) is considered a useful strategy. Although MSCs are commonly isolated by exploiting their plastic adherence, several studies have suggested that there are other populations of stem and/or osteoprogenitor cells that are removed from primary culture during media replacement. Therefore, we developed a three-dimensional (3D) culture system in which adherent and nonadherent stem cells are selected and expanded. Here, we described the characterization of 3D culture-derived cell populations in vitro and the capacity of these cells to differentiate into bone and/or cartilage tissue when placed inside of demineralized bone matrix (DBM) cylinders, implanted subcutaneously into the backs of rat for 2, 4, and 8 weeks. Our results demonstrates that 3D culture cells were a heterogeneous population of uncommitted cells that express pluripotent-, hematopoietic-, mesenchymal-, and endothelial-specific markers in vitro and can undergo osteogenic differentiation in vivo.
Keywords: Células madre hematopoyéticas; Huesos - Crecimiento; Stem/progenitor cells; Three-dimensional (3D) culture; Transforming growth factor-b1 (TGF-b1); Osteogenesis; Demineralized bone matrix